Evaluation of mechanical and fracture behaviour of POFA-FA-Metakaolin based geopolymer fibre reinforced concrete / Iftekhair Ibnul Bashar - Iftekhair, Ibnul Bashar (2014)
The depletion of natural resources, emission of CO2 from the cement industries and the waste products from industrial by-products pose irreparable danger to the ecological balance. There have been many attempts to replace ordinary Portland cement (OPC) and the aggregates through the use of industrial by-products and waste materials in recent years. In Malaysia, the availability of industrial by-products such as palm oil fuel ash (POFA) and fly ash (FA) could be considered as viable binders along with Metakaolin (MK) to develop geopolymer concrete (GC). In addition, other industrial by-products such as manufactured sand (M-sand) and oil palm shell (OPS) could ideally replace the conventional fine and coarse aggregates, respectively. This dissertation reports the development of POFA-FA-MK-based geopolymer concrete (PFMGC) using M-sand and OPS as fine and coarse aggregates, respectively. The mechanical properties of GC varying different proportion of POFA, FA and MK as binder was investigated. An appropriate mixture design for structural grade PFMGC is also proposed. The effect of steel fibres on the development of mechanical properties and fracture behaviour was investigated for two different aspect ratios (AR 80 and 65) and three different percent of volume as 0.25%, 0.50% and 0.75%. The ratios of Msand/ binder, OPS/ binder, water/ binder and alkaline solution/ binder were kept constant as 1.125, 0.375, 0.18 and 0.4, respectively. The specimens were cured in oven of 650C temperature for 48 hours and then kept in room temperature and relative humidity of 280C and 79%, respectively till the age of testing. The mechanical properties and the fracture behaviour of the fibre-reinforced PFMGC were compared with fibred and non-fibred concrete consisting OPS and crushed granite aggregate.The results show that the POFA-MK based geopolymer concrete (PMGC) achieved better strength than that of the PFMGC due to presence of the appropriate ratios of Silica/ Alumina, Sodium oxide (and Potassium oxide)/ Silica and Sodium oxide (and Potassium oxide)/ Alumina as 8.73, 0.11 and 0.93, respectively. The corresponding 28-day compressive strengths of concretes having 90% and 80% of POFA with MK as binder were 23.2 and 23.6 MPa, respectively. The highest values of the splitting tensile strength and flexure strength of 2.14 MPa and 3.41 MPa were obtained for the binder consisting 90% of POFA and 10% of MK. The early strength development at the age of 3-day was found above 80% and this is attributed to geopolymerization process at high temperature. The low values of static modulus of elasticity and the Poisson’s ratio of 6.36 GPa and 0.176, respectively for PMGC (POFA: MK=90:10) is due to the low stiffness of OPS aggregate. The stress-strain relations of PMGC fit well with the expression developed for OPC concrete. The flexural strength, splitting tensile strength and fracture behaviour were significantly affected by the AR and the volume of steel fibres. The addition of steel fibre with AR of 80 produced higher splitting tensile & flexural strengths and total fracture energy, respectively of 5%, 6% and 50-80% compared to results of the corresponding values with steel fibre with AR of 65.